2023
DOI: 10.3390/nu15061518
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Supplementation Attenuates Inflammation and Oxidative Stress Induced by Chronic Sleep Restriction

Abstract: Background: Insufficient sleep is a serious public health problem in modern society. It leads to increased risk of chronic diseases, and it has been frequently associated with cellular oxidative damage and widespread low-grade inflammation. Probiotics have been attracting increasing interest recently for their antioxidant and anti-inflammatory properties. Here, we tested the ability of probiotics to contrast oxidative stress and inflammation induced by sleep loss. Methods: We administered a multi-strain probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Probiotics are implicated in the enhancement of intestinal permeability, regulation of immune function, and reduction of pro-inflammatory cytokines 53 . Additionally, it has been demonstrated that probiotic bacteria and/or bacterial metabolites affect the host by changing the amounts of both endogenous and exogenous ROS resulting in oxidative stress reduction 54 .
Figure 3 Effect of the produced microcapsules on stomach inflammatory and oxidative markers.
…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics are implicated in the enhancement of intestinal permeability, regulation of immune function, and reduction of pro-inflammatory cytokines 53 . Additionally, it has been demonstrated that probiotic bacteria and/or bacterial metabolites affect the host by changing the amounts of both endogenous and exogenous ROS resulting in oxidative stress reduction 54 .
Figure 3 Effect of the produced microcapsules on stomach inflammatory and oxidative markers.
…”
Section: Resultsmentioning
confidence: 99%
“…The chronic fatigue syndrome (CFS) mouse model was established using a modified method as previously described [ 36 , 37 ]. All mice adapted to the laboratory environment for one week and according to the experimental requirements were randomly selected and divided into groups (6 mice per group).…”
Section: Methodsmentioning
confidence: 99%
“…The imbalance of prooxidants and antioxidants of diet could contribute to sleep disorders [ 5 8 ]. However, little epidemiological evidence has focused on the total antioxidant property of diet in the pathogenesis of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%